2002
DOI: 10.1088/0264-9381/19/9/303
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for a decaying cosmological constant

Abstract: A mechanism is introduced to reduce a large cosmological constant to a sufficiently small value consistent with the observational upper limit. The basic ingradient in this mechanism is a distinction which has been made between the two unit systems used on cosmology and particle physics. We have used a conformal invariant gravitational model to define a particular conformal frame in terms of the large scale properties of the universe. It is then argued that the contributions of mass scales in particle physics t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…Similarly, when ε > 0 the reverse is true, namely that matter is annihilated and the direction of energy transfer is outside of the matter system so that the rate of dilution is faster than the standard one. Even though β and ε in (22) are generally evolving functions, we consider the case that they can be regarded as constant parameters. The constancy of β means that we fix the arbitrary coupling function h(ϕ) to have an exponential form h(ϕ) = e β ϕ Mp .…”
Section: The Cosmological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, when ε > 0 the reverse is true, namely that matter is annihilated and the direction of energy transfer is outside of the matter system so that the rate of dilution is faster than the standard one. Even though β and ε in (22) are generally evolving functions, we consider the case that they can be regarded as constant parameters. The constancy of β means that we fix the arbitrary coupling function h(ϕ) to have an exponential form h(ϕ) = e β ϕ Mp .…”
Section: The Cosmological Settingmentioning
confidence: 99%
“…This choice as a first approximation is more restrictive but greatly simplifies the mathematics and does not affect the basics of our arguments. In these cases, (22) reduces to ϕ M p = γ ln a…”
Section: The Cosmological Settingmentioning
confidence: 99%
“…Combining (8) and (11) leads to 12) where ψ 2 = α. Note that σ appears as a dynamical field which allows us to investigate the evolution ofm as the universe evolves.…”
Section: The Modelmentioning
confidence: 99%
“…This usually leads to the variability of the fundamental constants. Recently, it is shown that one can use this dynamical distinction between two unit systems usually used in cosmology and particle physics to alleviate the cosmological constant and coincidence problems [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%